COUNTDOWN TOOLS NUMBER OF PEOPLE IN THE ROOM LIGHT SENSOR (LDR) MICROCONTROLLER BASED AT89C51 - Mochammad Rifal; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Komputer, 2008)
This paper tries to introduce something a tool designed to counter Number of people who aim to be able to monitor the number of people in a room and show it on a seven segment display. This instrument is equipped with an alarm. Alarm Buzzer be useful to know if anyone who came into the room. This instrument is based on AT89C51 microcontroller, in which programs written in Assembler programming language. The sensor used is the Light Sensor (LDR), display using two seven segment, and a Buzzer alarm. This instrument is designed to be able to count the number of people within range of 00 to 99 people.